A Unique Case of Low-Grade Mucinous Neoplasm in Stump Appendectomy - Mohannad Al-Tarakji; Syed Muhammad Ali; Amjad Ali Shah; Mahir Abdulla Petkar; Salman Mirza; Rajvir Singh; Ahmad Zarour (Case Reports in Surgery)
Background. We describe a case of a young male with a history of appendectomy one year ago, who developed symptoms of stump appendicitis, and after removing this stump, histopathology showed low grade neoplasm. Summary. Stump appendicitis is an uncommon complication after appendectomy and may lead to serious complications. Management of low-grade appendiceal mucinous neoplasm (LAMN) is controversial, and we discuss the importance of the case. Conclusion. The case of young male post stump appendectomy with histopathology showing LAMN in the stump of the appendix, which to our knowledge, is the first in the medical literature and, discuss the stump appendicitis and incomplete appendectomy concerning malignancy, mucinous neoplasm, and adenocarcinoma.